Transiently Nav1.8-expressing neurons are capable of sensing noxious stimuli in the brain - Tenza-Ferrer, Helia; Collodetti, Mélcar; Nicolau, Eduardo de Souza; Birbrair, Alexander; Magno, Luiz Alexandre Viana; Romano-Silva, Marco Aurélio (Frontiers in Cellular Neuroscience, 2022)
While current research highlights the role of Nav1.8 sensory neurons from the peripheral nervous system, the anatomical and physiological characterization of encephalic Nav1.8 neurons remains unknown. Here, we use a Cre/fluorescent reporter mouse driven by the Nav1.8 gene promoter to reveal unexpected subpopulations of transiently-expressing Nav1.8 neurons within the limbic circuitry, a key mediator of the emotional component of pain. We observed that Nav1.8 neurons from the bed nuclei of the stria terminalis (BST), amygdala, and the periaqueductal gray (vPAG) are sensitive to noxious stimuli from an experimental model of chronic inflammatory pain. These findings identify a novel role for central Nav1.8 neurons in sensing nociception, which could be researched as a new approach to treating pain disorders.